(untitled) (Global Journal of Human-Social Science, 2017)
In this empirical statewide multiyear analysis the extent to which the academic performance of students enrolled in special education was influenced by school district student enrollment was determined Five years of Texas statewide data on the Texas Assessment Knowledge Skills Reading Mathematics Science Social Studies and Writing exams were analyzed as a function of three school district sizes a small-size up to 1 599 students b moderate-size 1 600 to 9 999 students and c large-size 10 000 or more students Inferential statistical procedures revealed that students in special education who were enrolled in large-size school districts had statistically significantly higher passing rates on all five exams than did students in special education who were enrolled in either moderate-size or small-size school districts for all 5 years Effect sizes were small